Papillomavirus in Wildlife - Frias-De-Diego, Alba; Jara, Manuel; Escobar, Luis E. (Frontiers in Ecology and Evolution, 2019)
Papillomaviruses (PV) are associated with epithelial malignancies in animals, including cancer in humans. Limited knowledge exists regarding the evolutionary history of non-human PV. We assessed the phylogeography of PV with emphasis in wildlife hosts. We explored the phylogenetic, geographic, and environmental relationships of PV and hosts applying Bayesian inference and spatial analyses of virus and hosts. We found that the available wildlife PV data support previous reports on the higher incidence of fibropapillomatosis over carcinoma in humans and wildlife, being mammals the most common host. We also found geographic bias on the available wildlife papillomavirus (WPV) information towards the Northern Hemisphere, which may have influenced our results to show Europe as the most likely origin of the available WPV lineages. Therefore, we highlight the need for detailed studies on the presence of WPV in regions and species not included in this study (e.g., reptiles from the tropics) to better inform sites of WPV origin, susceptible species, and spillover potential. Future studies of the clinical and subclinical occurrence, distribution, and phylogenetic signatures of WPV may help understand the spread, virulence, and epidemiology of PV in general. From an evolutionary perspective, our overview suggests that WPV are a promising host-pathogen system to untangle questions regarding co-evolution due to its large geographic distribution and occurrence in a wide variety of aquatic and terrestrial wildlife species.